Sanctions as tools in the US foreign policy after the cold war - Joksimović Aleksandra (Međunarodni Problemi)
In searching for various opportunities to act in pursuing its foreign policy and endeavors to achieve a dominant role in the global processes USA has developed a broad range of instruments including a financial assistance as a way to be given support for its positions, intelligence activities, its public diplomacy, unilateral implementation of sanctions and even military interventions. The paper devotes special attention to one of these instruments - sanctions, which USA implemented in the last decade of the 20th century more than ever before. The author explores the forms and mechanisms for implementation of sanctions, the impact and effects they produce on the countries they are directed against, but also on the third parties or the countries that have been involved in the process by concurrence of events and finally on USA as the very initiator of imposing them.